-96=-8(b+7)

Simple and best practice solution for -96=-8(b+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -96=-8(b+7) equation:


Simplifying
-96 = -8(b + 7)

Reorder the terms:
-96 = -8(7 + b)
-96 = (7 * -8 + b * -8)
-96 = (-56 + -8b)

Solving
-96 = -56 + -8b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '8b' to each side of the equation.
-96 + 8b = -56 + -8b + 8b

Combine like terms: -8b + 8b = 0
-96 + 8b = -56 + 0
-96 + 8b = -56

Add '96' to each side of the equation.
-96 + 96 + 8b = -56 + 96

Combine like terms: -96 + 96 = 0
0 + 8b = -56 + 96
8b = -56 + 96

Combine like terms: -56 + 96 = 40
8b = 40

Divide each side by '8'.
b = 5

Simplifying
b = 5

See similar equations:

| y^2-2y+1-x=0 | | 85(7+m)=1955 | | X+y=186 | | -10=-7u+3(u-2) | | 10-3f=-4f | | -(1+n)=-5n+5(1+2n) | | x^2-2xy+3x-6y=0 | | (-3w)=-10-4w | | 3x-32=-7x+5 | | 2x-8=-32 | | 5x^3+6x^2=0 | | (-5-6i)(7+8i)= | | 30u+4=10 | | b-9=4b | | g=3x-(2+x)(4x-3) | | 497*x=-20 | | 7(2x+14)=210 | | 3x+6=2(3x+12) | | -5+2a=3a+2 | | 42-4y=3y | | 64+4y=3y | | 5(2.95-a)=47.75 | | -(x-8)=2(x-6)+10 | | 140+10x=20+12x+x^2 | | 64+7u=15u | | (-2x+9)=0 | | 3(j+5)=(11-j) | | 9x^4+3x^3=0 | | 7x+499= | | (.5x-5)=0 | | 3u=28-u | | 2ab+4c= |

Equations solver categories